[I060] Working in radiotherapy from the perspective of an MRI physicist. (August 2018) - Olsson, Lars E.
Abstract : There is a substantial increase of imaging in the recent development in radiotherapy. The on-going process of installing dedicated radiotherapy MR-scanners in the oncology/radiotherapy clinics is an obvious proof of this development. MRI is a much more complex modality and applications extend from diagnosis to specific imaging for target identification, treatment planning, treatment follow-up and adaptive regimes. An in-house MR-scanner also brings along many safety issues, both for personnel and patients. Altogether, there is an increasing need for MRI expertise in the radiotherapy department. The demand on reliability and quantification of the data is considerably larger in therapy than diagnostic MRI applications. That means that what can easily be accepted as a well know harmless artefacts in the diagnostic setting can have detrimental negative effects if used for treatment guidance in radiotherapy. Therefore, the MRI-physicist needs specific training in how the image data will be used in the radiotherapy workflow. The MRI-expertise can be an in-house MRI-physicist working with radiotherapy or as a service provided by diagnostic radiology physicists. In any case, it is important that the MRI-physicist will be specifically trained and dedicated to radiotherapy. Not all MRI-physicists from radiology can have the knowledge needed in radiotherapy. Similarly, an MRI-physicist working in radiotherapy cannot be an expert on all MRI techniques. An ideal model is to have a dedicated MRI-physicist in-house in radiotherapy, which will act as a link to the other MRI-physicists in radiology, and thereby facilitate the discussion and knowledge transfer in both directions. The present question will be even more important to discuss when hybrid modalities, such as MR-linacs, will be implemented in the clinics. It is obvious that the MR-scanner is a part of the treatment machine. Therefore, the installation of MR-linacs should be combined with recruitment of in-house MRI-expertise. Traditionally, there have been different physicists dedicated to radiotherapy, nuclear medicine, MRI and other radiology. The future hybrid modalities in both diagnostics (PET/MR, PET/CT) and therapy (MR/linac) will be the end of the era for "One Modality Physicist". This is a great challenge to the physics profession.